A ruthenium-yttrium oxide-based composite material and its preparation method and application
A ruthenium-yttrium oxide-based composite material with a ruthenium-iridium alloy surface enhances hydrogen evolution catalysis, addressing high energy consumption in water electrolysis by improving catalytic activity and stability, making it a cost-effective alternative to platinum catalysts.
Patent Information
- Application Number
- CN202410860353.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Current water electrolysis hydrogen production technologies face high energy consumption due to the scarcity and high cost of platinum catalysts, and existing ruthenium oxide-based materials are not effective for hydrogen evolution catalysis due to weak active sites for hydrogen adsorption, limiting their use in large-scale applications.
A ruthenium-yttrium oxide-based composite material is developed with a ruthenium-iridium alloy on its surface, enhanced by iridium doping, which improves hydrogen evolution catalytic activity and stability through controlled thermal reduction processes.
The composite material achieves high catalytic activity and stability for hydrogen evolution, reducing energy consumption and costs, with performance comparable to commercial platinum catalysts, and is suitable for large-scale production.
Smart Images

Figure CN118621362B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a ruthenium-yttrium oxide-based composite material and a preparation method and application thereof. Background Art
[0002] With the development of economy and society, the market is pursuing cleaner energy with richer energy storage. Water electrolysis hydrogen production uses abundant and renewable water as raw material to produce hydrogen, and the process is green and pollution-free. Therefore, water electrolysis hydrogen production has been widely accepted and supported by the society as a clean energy solution. However, water electrolysis hydrogen production technology currently has problems such as high energy consumption (per 1m3 of hydrogen produced). 3 Hydrogen requires 5-7kWh of electricity. In order to save energy consumption in the production of hydrogen by electrolysis of water, a catalyst can be added during the production of hydrogen. The precious metal platinum (Pt) is currently recognized as the best catalyst for the hydrogen evolution reaction, but the scarce reserves and high prices of Pt-based catalysts restrict its large-scale use in the technology of hydrogen production by electrolysis of water. Therefore, the search for new hydrogen evolution reaction catalysts that can replace the precious metal Pt has become a current technical hotspot and difficulty.
[0003] The price of ruthenium (Ru) is only one-twelfth of that of Pt, and its cost is significantly lower than that of Pt. Ruthenium oxide-based materials have begun to be used in oxygen evolution catalysis in water electrolysis. For example, yttrium ruthenate (Y2Ru2O7) with a pyrochlore structure (A2B2O7) has been reported to have electrochemical oxygen evolution catalytic activity and stability that surpass RuO2 in the oxygen evolution reaction. The mass fraction of Ru in yttrium ruthenate is about 41wt.%, which is much lower than RuO2 (76wt.%), which further reduces the cost of oxygen evolution catalysts. However, the potential, reaction site, reaction mechanism, etc. of oxygen evolution catalysis and hydrogen evolution catalysis are different. The fact that ruthenium oxide-based materials can be used as oxygen evolution catalysts does not mean that they can be used as hydrogen evolution catalysts. The active sites of ruthenium oxide are too weak for hydrogen adsorption. Current research on yttrium ruthenate is mainly focused on the field of oxygen evolution catalytic performance, and there are few reports on its electrocatalytic hydrogen evolution performance.
[0004] In view of the good oxygen evolution performance of ruthenium oxide, many researchers have begun to study ruthenium oxide-based hydrogen evolution catalysts in order to form high-performance bifunctional catalysts that can be used in overall water decomposition, which is of practical significance for reducing the process and structural costs of membrane electrodes. Synthesizing multi-electrocatalysts is an effective method to improve the performance of ruthenium oxide hydrogen evolution reaction. The principle is to use the different adsorption capacities of hydrogen between the components to transfer hydrogen from the hydrogen-rich phase to the hydrogen-poor phase, and work synergistically to enhance the hydrogen evolution activity of the catalyst surface. In the current related reports, most researchers use the method of preparing multi-electrocatalysts by mixing ruthenium oxide with a carrier to form a composite material. However, on the one hand, this type of synthesis method is difficult to controllably construct a stable chemical interface, resulting in poor long-term stability of the catalyst. On the other hand, it is also impossible to achieve directional loading of the catalyst, which limits the optimization of the catalyst structure and the improvement of catalytic performance.
[0005] Therefore, developing a precise, controllable and simple method for directional loading of ruthenium oxide-based composites and improving their hydrogen evolution catalytic performance has important scientific significance and application value. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a ruthenium-yttrium oxide-based composite material having excellent hydrogen evolution catalytic activity and catalytic stability.
[0007] The present invention also provides a method for preparing the ruthenium-yttrium oxide-based composite material.
[0008] The present invention also provides application of the ruthenium-yttrium oxide-based composite material.
[0009] According to an embodiment of the first aspect of the present invention, a ruthenium-yttrium-based composite material is provided. The ruthenium-yttrium oxide-based composite material includes yttrium-ruthenium-iridium oxide and a ruthenium-iridium alloy formed on the surface thereof.
[0010] The ruthenium-yttrium based composite material according to the embodiment of the present invention has at least the following beneficial effects:
[0011] Compared with the traditional yttrium ruthenate material, the ruthenium-yttrium oxide-based composite material provided by the present invention is doped with iridium on the basis of yttrium ruthenate, and a ruthenium-iridium alloy is formed on its surface; the combination of the two can significantly improve the hydrogen evolution catalytic activity and reduce the hydrogen evolution potential. Specifically:
[0012] Iridium metal has a unique electronic structure and can effectively participate in the adsorption and activation process of hydrogen molecules. Its electronic structure helps to optimize the intermediate state of the reaction and reduce the reaction energy barrier. Iridium metal has a high density of active sites, which can effectively participate in the adsorption, dissociation and electron transfer process of hydrogen molecules, thereby improving the catalytic efficiency. That is, iridium doping can improve the hydrogen evolution catalytic activity of the obtained ruthenium-yttrium oxide-based composite material to a certain extent.
[0013] The alloying of Ru and Ir improves the electronic structure of the resulting ruthenium-yttrium oxide-based composite material, making it easier to adsorb and activate hydrogen molecules, thereby improving the catalytic activity. Nanoscale alloy particles can significantly improve the catalytic performance of the hydrogen evolution reaction due to their higher surface area and more active sites. In other words, the formation of the ruthenium-iridium alloy further improves the catalytic activity of hydrogen evolution.
[0014] According to some embodiments of the present invention, in the ruthenium-yttrium oxide-based composite material, the molar ratio of yttrium, ruthenium and iridium is 2:2-x:x; and 0<x<2.
[0015] According to some embodiments of the present invention, the particle size of the ruthenium-iridium alloy is 1 to 3 nm.
[0016] According to some embodiments of the present invention, the particle size of the ruthenium-yttrium oxide-based composite material is 80-120 nm, for example, specifically about 100 nm.
[0017] According to an embodiment of the second aspect of the present invention, a method for preparing the ruthenium-yttrium oxide-based composite material is provided, and the preparation method comprises the following steps:
[0018] S1. synthesizing a precursor in an oxide state, wherein the precursor includes yttrium, ruthenium and iridium; S2. thermally reducing the precursor.
[0019] The mechanism of the preparation method is as follows:
[0020] In step S2, thermal reduction is performed, and the iridium and ruthenium on the surface of the precursor in an oxide state are reduced from the oxide state to a single alloy state, and then segregated on the surface to form nanoparticles.
[0021] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0022] In actual production, the amount of iridium doping can be controlled by controlling the material ratio of yttrium, ruthenium, and iridium in the precursor in step S1; the segregation of the ruthenium-iridium alloy can be controlled by controlling the temperature and duration of the thermal reduction in step S2, specifically, the segregation amount, particle size, particle size distribution, and electronic structure of the obtained ruthenium-yttrium oxide-based composite material can be controlled to obtain a ruthenium-yttrium oxide-based composite material with multiple active components and high-performance electrochemical hydrogen evolution reaction catalytic performance. Further, in the preparation method provided by the present invention, the ruthenium-iridium alloy is segregated from an oxide containing yttrium, ruthenium, and iridium in an oxide state, so the two parts of the obtained ruthenium-yttrium oxide-based composite material are tightly combined, and the chemical interface is stable, thereby also improving its catalytic stability as a hydrogen evolution catalyst.
[0023] In summary, the present invention provides an accurate, controllable and simple directional loading method, with simple raw materials, easy process flow, suitable for large-scale preparation, green and safe reaction process, no other toxic additives, and the ruthenium-yttrium oxide-based composite material prepared by the method has higher catalytic activity and stability when used as a hydrogen evolution catalyst. The preparation method provided by the present invention has important scientific significance and application value for exploring the design and preparation of other types of multi-component catalytic systems and their applications.
[0024] According to some embodiments of the present invention, in step S1, the method for synthesizing the precursor comprises the following steps:
[0025] S1a. The Y salt, Ru salt, Ir salt and complexing agent are mixed in water and dried;
[0026] S1b. calcining the solid product obtained in step S1a in an oxygen-containing atmosphere.
[0027] The reaction mechanism of step S1 is as follows:
[0028] In step S1a, during the mixing reaction, the solvent evaporates and the concentration in the mixed reaction system increases, which causes the ions corresponding to Y, Ru, and Ir to approach the complexing agent and form a gel.
[0029] In step S1a, under the action of the complexing agent, yttrium, ruthenium and iridium are evenly distributed, and after drying, solid particles with uniform texture are formed, and the solid particles are mainly water-insoluble hydroxides, etc.;
[0030] In step S1b, the solid particles are calcined in an oxygen-containing atmosphere to transform into the corresponding yttrium ruthenium iridium oxide (also known as iridium-doped yttrium ruthenate).
[0031] According to some embodiments of the present invention, in step S1a, the complexing agent includes citric acid.
[0032] According to some embodiments of the present invention, in step S1a, the molar volume ratio of the complexing agent to water is 0.05-0.06 mol / L, for example, about 0.055 mol / L.
[0033] According to some embodiments of the present invention, in step S1a, the Y salt includes at least one of yttrium nitrate, yttrium nitrate hydrate, yttrium trichloride and yttrium trichloride hydrate.
[0034] According to some embodiments of the present invention, in step S1a, the Ru salt includes at least one of ruthenium chloride, ruthenium chloride hydrate and ruthenium nitrosyl nitrate.
[0035] According to some embodiments of the present invention, in step S1a, the Ir salt includes at least one of iridium chloride and a hydrate thereof.
[0036] According to some embodiments of the present invention, in step S1a, the addition ratio of the Y salt, Ru salt, and Ir salt is such that the molar ratio of Y, Ru, and Ir is 2:2-x:x; and 0<x<2. For example, 0.01≤x≤1.9; more specifically, x is about 0.02, 0.04, 0.05, 0.1, 0.15, 0.2, 0.3, 0.5, or about 1.0.
[0037] Thus, the chemical formula of the precursor can be expressed as Y2Ru 2-x Ir x O7. That is, in the precursor, the molar ratio of Y, Ru and Ir is 2:2-x:x.
[0038] According to some embodiments of the present invention, in step S1a, the molar ratio of the sum of the moles of Y, Ru and Ir in the Y salt, Ru salt and Ir salt to the molar ratio of the citric acid is 0.8 to 1.2:1, for example, specifically about 1:1.
[0039] According to some embodiments of the present invention, step S1a further includes dripping an acid solution in the mixed reaction. The acid solution includes a 68-70% nitric acid aqueous solution. This can avoid hydrolysis and precipitation of the Y salt, Ru salt, and Ir salt. The amount of the acid solution to be dripped is based on the absence of visible hydrolysis and precipitation. When the reaction volume is small, generally only one drop (about 0.05 mL) is required.
[0040] According to some embodiments of the present invention, in step S1a, the temperature of the mixing reaction is 80-100°C, for example, about 90°C.
[0041] According to some embodiments of the present invention, in step S1a, the duration of the mixing reaction is 4 to 6 hours, for example, specifically about 5 hours.
[0042] According to some embodiments of the present invention, in step S1a, the mixing reaction is carried out under stirring, which can not only improve mass transfer, but also increase the evaporation rate of the solvent and accelerate the formation of gel.
[0043] According to some embodiments of the present invention, in step S1a, the drying temperature is 150-200°C, for example, about 160°C, 170°C, 180°C or about 190°C.
[0044] According to some embodiments of the present invention, in step S1a, the drying time is 5 to 8 hours, for example, about 6 hours or about 7 hours.
[0045] According to some embodiments of the present invention, in step S1b, the oxygen-containing atmosphere includes at least one of air and oxygen.
[0046] According to some embodiments of the present invention, in step S1b, the calcination includes a first stage of constant temperature and a second stage of constant temperature performed sequentially.
[0047] According to some embodiments of the present invention, the temperature of the first stage constant temperature is 600-650° C. For example, it may be about 620° C.
[0048] According to some embodiments of the present invention, the duration of the first stage of constant temperature is 5 to 7 hours, for example, specifically about 6 hours.
[0049] According to some embodiments of the present invention, the temperature of the second stage of constant temperature is 1000-1100° C. For example, it may be about 1050° C.
[0050] According to some embodiments of the present invention, the duration of the second stage of constant temperature is 7 to 9 hours, for example, specifically about 8 hours.
[0051] According to some embodiments of the present invention, in step S1b, the heating rate of the calcination is 3 to 10°C / min. For example, it may be about 5°C / min or about 6°C / min. It should be noted that the heating rates from room temperature to the first stage constant temperature and from the first stage constant temperature to the second stage constant temperature may be the same or different.
[0052] According to some embodiments of the present invention, step S1b further includes cooling after the calcination.
[0053] According to some embodiments of the present invention, in step S2, the thermal reduction atmosphere includes hydrogen.
[0054] According to some embodiments of the present invention, in step S2, the thermal reduction atmosphere is a mixture of hydrogen and argon, wherein the volume percentage of hydrogen is 3-8%, for example, specifically about 5%.
[0055] According to some embodiments of the present invention, in step S2, the gas flow rate of the thermal reduction is 150-250 sccm, for example, about 200 sccm.
[0056] According to some embodiments of the present invention, in step S2, the temperature of the thermal reduction is 300-550°C, for example, about 350°C, 400°C, 450°C or about 500°C.
[0057] According to some embodiments of the present invention, in step S2, the duration of the thermal reduction is 4 to 10 hours, for example, about 6 hours, 8 hours or about 9 hours.
[0058] According to some embodiments of the present invention, in step S2, the heating rate of the thermal reduction is 3-10°C / min, for example, about 5°C / min or about 6°C / min.
[0059] According to some embodiments of the present invention, step S2 further includes cooling after the thermal reduction.
[0060] According to an embodiment of the third aspect of the present invention, there is provided a hydrogen evolution catalyst, wherein the raw material for preparing the hydrogen evolution catalyst comprises the ruthenium-yttrium oxide-based composite material.
[0061] Since the hydrogen evolution catalyst adopts all the technical solutions of the ruthenium-yttrium oxide-based composite material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0062] According to some embodiments of the present invention, the hydrogen evolution catalyst may be the ruthenium-yttrium oxide-based composite material itself, or a mixture of the ruthenium-yttrium oxide-based composite material and an auxiliary agent, wherein the auxiliary agent includes at least one of a conductive agent and a binder.
[0063] According to some embodiments of the present invention, the hydrogen evolution catalyst also has acidic oxygen evolution catalytic activity, so it can be used alone as a hydrogen evolution catalyst in water electrolysis, or as a bifunctional catalyst.
[0064] According to an embodiment of the fourth aspect of the present invention, there is provided a use of the hydrogen evolution catalyst in water electrolysis.
[0065] Since the application adopts all the technical solutions of the hydrogen evolution catalyst of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0066] According to some embodiments of the present invention, the application includes electrolyzing water in a three-electrode system; wherein the hydrogen evolution catalyst is supported on the working electrode.
[0067] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0068] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0069] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0071] Figure 1 It is the XRD spectrum of the ruthenium-yttrium oxide-based composite material obtained in Examples 1 to 3 of the present invention and Comparative Example 1;
[0072] Figure 2 is a HRTEM image of the ruthenium-yttrium oxide-based composite material obtained in Example 1 of the present invention;
[0073] Figure 3 These are the polarization curves of the ruthenium-yttrium oxide-based composite materials obtained in Examples 1 to 3 of the present invention and Comparative Example 1, as well as the commercial platinum-carbon catalyst;
[0074] Figure 4 are polarization curves of the ruthenium-yttrium oxide-based composite materials obtained in Examples 1, 4 to 5 of the present invention and the commercial platinum-carbon catalyst;
[0075] Figure 5 are polarization curves of the ruthenium-yttrium oxide-based composite materials obtained in Examples 1, 6 to 7 of the present invention and the commercial platinum-carbon catalyst;
[0076] Figure 6 This is the polarization curve of the ruthenium-yttrium oxide-based composite material obtained in Example 1 of the present invention before and after 2000 cycles of CV testing. DETAILED DESCRIPTION
[0077] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0078] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0079] Example 1
[0080] In this example, a ruthenium-yttrium oxide-based composite material was prepared, and the specific steps were as follows:
[0081] S1. Synthesis of Precursors
[0082] S1a. According to the molar ratio of 2:1.7:0.3:4, yttrium nitrate (Y(NO3)3·6H2O, 0.8mmol), ruthenium trichloride (RuCl3, 0.68mmol), iridium trichloride (IrCl3, 0.12mmol) and citric acid (1.6mmol) are dissolved in 30mL of deionized water, and 1ml of nitric acid solution (concentration 68-70%, i.e. commercially available concentrated nitric acid is directly used) is added dropwise.
[0083] The resulting mixture was placed in a water bath, set to 90 °C and heated for 5 h while continuously stirring the solution magnetically;
[0084] The prepared gel was placed in a drying oven and kept at 170°C for 6 hours to obtain dry powder.
[0085] S1b. The dried powder obtained in step S1a was transferred to a corundum crucible and placed in a muffle furnace for heating (air atmosphere). The temperature was raised from room temperature to 600°C at a rate of 5°C / min and kept at a constant temperature for 6 hours; then the temperature was raised to 1050°C at a rate of 5°C / min and kept at a constant temperature for 8 hours. After the procedure was completed and the muffle furnace was cooled to room temperature, Y2Ru 1.7 Ir 0.3 O7 material (calcined product, also known as iridium-doped yttrium ruthenate).
[0086] S2. The obtained Y2Ru 1.7 Ir 0.3 O7 is placed in a tube furnace, and a 5% H2 / Ar mixed gas is introduced into the tube furnace at a flow rate of 200 sccm. The tube furnace is ventilated for 1 hour before heating to remove the air in the tube furnace. Then, the tube furnace is heated from room temperature to 450°C at a heating rate of 5°C / min, kept at a constant temperature for 8 hours, and then naturally cooled to room temperature to obtain a ruthenium-yttrium oxide-based composite material.
[0087] Example 2
[0088] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0089] In step S2, the constant temperature time of thermal reduction is 10 hours.
[0090] Example 3
[0091] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0092] In step S2, the constant temperature time of thermal reduction is 4 hours.
[0093] Example 4
[0094] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0095] In step S2, the constant temperature of thermal reduction is 300°C.
[0096] Example 5
[0097] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0098] In step S2, the constant temperature of thermal reduction is 550°C.
[0099] Example 6
[0100] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0101] In step S1a, the amount of ruthenium trichloride is 0.76 mmol; the amount of iridium trichloride is 0.04 mmol.
[0102] Example 7
[0103] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0104] In step S1a, the amount of ruthenium trichloride is 0.64 mmol; the amount of iridium trichloride is 0.16 mmol.
[0105] Comparative Example 1
[0106] This example prepares a ruthenium-yttrium oxide-based composite material, which is different from Example 1 in that:
[0107] Step S2 is not included.
[0108] Test Case
[0109] In the first aspect of this example, the morphology, material and crystallization properties of the ruthenium-yttrium oxide-based composite materials obtained in the examples and comparative examples were tested. The specific testing methods included XRD and transmission electron microscopy.
[0110] The results show that as the thermal reduction time in step S2 increases, the characteristic peak of the ruthenium-iridium alloy (indicated by RuIr in the figure, PDF 01-0791-9300) in the obtained ruthenium-yttrium oxide-based composite material becomes more and more obvious. If thermal reduction is not performed, the characteristic peak of the ruthenium-iridium alloy will not appear; and all ruthenium-yttrium oxide-based composite materials have obvious characteristic peaks of yttrium ruthenate (indicated by YRO in the figure, PDF 83-0637); it should be noted that iridium is indeed doped in yttrium ruthenate, but due to the limited doping amount, it only affects the peak position of yttrium ruthenate to a small extent and does not produce new characteristic peaks. The specific XRD test results are as follows: Figure 1 As shown; Figure 1 In the figure, YRIO is the ruthenium-yttrium oxide-based composite material obtained in Comparative Example 1, and YRIO-4H, YRIO-8H and YRIO-10H correspond to the products of Example 3, Example 1 and Example 2, respectively.
[0111] The test results also show that after thermal reduction, metal nanoparticles are eluted from the substrate material on the surface. The HRTEM image shows that the lattice spacing is 0.210nm, which is the (002) plane of the RuIr alloy. The HRTEM image also shows a crystalline phase with a lattice spacing of 0.307nm, and the Y2Ru 1.7 Ir 0.3 The (311) plane of the O7 material matches. This shows that the ruthenium yttrium oxide-based composite material obtained in the present invention is indeed composed of yttrium ruthenium iridium oxide and the ruthenium iridium alloy segregated therein. In addition, it can be concluded from the wide-view HRTEM image that the average particle size of the obtained ruthenium yttrium oxide-based composite material is about 100nm, and the particle size of the ruthenium iridium alloy particles measured from the small-view HRTEM image is between 1 and 3nm. Specifically, the HRTEM image of the ruthenium yttrium oxide-based composite material obtained in Example 1 is as follows Figure 2 shown.
[0112] In the second aspect of this example, the ruthenium-yttrium oxide-based composite material prepared in the embodiment and the comparative example was used as a hydrogen evolution catalyst to test its performance in hydrogen evolution in water electrolysis. The specific test method is:
[0113] Preparation of working electrode: 5 mg of catalyst (product of the examples and comparative examples, and commercial 20 wt.% Pt / C (produced by Johnson Matthey)) and 1 mg of carbon black were dispersed in a mixed solution of 0.8 mL of water, 0.17 mL of isopropanol and 0.03 mL of 5 wt.% Nafion. After ultrasonic homogenization, 10 uL of the suspension was transferred and dropped on the polished glassy carbon electrode surface and dried naturally.
[0114] Hydrogen evolution performance test: The above-prepared electrode was used as the working electrode, saturated calomel (SCE) as the reference electrode, carbon rod as the counter electrode, and 0.5M H2SO4 aqueous solution as the electrolyte to conduct hydrogen evolution performance test on an electrochemical workstation. The hydrogen evolution catalytic performance (50mA cm -2 or 100mA cm -2 ).
[0115] By applying 10 mA cm to the working electrode -2 Working current density, measuring the change of electrode voltage over time (more than 10h), that is, evaluating the electrochemical hydrogen evolution stability of the catalyst through chronopotentiometry curve. Specifically, CV test is performed with a voltage range from 0.14V to -0.04V (relative to reversible hydrogen electrode, RHE) and a scan rate of 100mv / s.
[0116] Example 1, Example 2, Example 3, commercial platinum-carbon catalyst and comparative example 1 at 50 mA cm -2 The corresponding hydrogen evolution overpotentials are 40mV, 45mV, 53mV, 48mV and 148mV, respectively. It can be seen that when the ruthenium-yttrium oxide-based composite material provided by the present invention is used for hydrogen evolution catalysis, its catalytic activity is equivalent to or higher than that of the commercial platinum-carbon catalyst; in addition, the ruthenium-iridium alloy phase produced by thermal reduction has a significant effect on the improvement of hydrogen evolution catalytic activity, and with the increase of thermal reduction time (increase in the proportion of ruthenium-iridium alloy phase), the catalytic performance of the obtained ruthenium-yttrium oxide-based composite material shows a trend of first increasing and then decreasing. The corresponding test results are as follows Figure 3 shown.
[0117] Example 1, Example 4 and Example 5 at 50 mA cm -2 The corresponding hydrogen evolution overpotentials are 40mV, 67mV and 69mV respectively. It can be seen that with the increase of thermal reduction temperature, the hydrogen evolution catalytic activity of the obtained ruthenium-yttrium oxide-based composite material first increases and then decreases. The corresponding test results are shown in Figure 4 shown.
[0118] Example 1, Example 6 and Example 7 at 50 mA cm -2The corresponding hydrogen evolution overpotentials are 40mV, 47mV and 69mV respectively. It can be seen that in the obtained ruthenium-yttrium oxide-based composite material, with the increase of iridium doping amount, its hydrogen evolution catalytic activity shows a trend of first increasing and then decreasing. The specific results are as follows Figure 5 shown.
[0119] The first polarization curve of the ruthenium-yttrium oxide-based composite material obtained in Example 1 is compared with the polarization curve after 2000 cycles of CV. The catalytic performance is comparable and almost no attenuation is shown. It can be seen that the ruthenium-yttrium oxide-based composite material provided by the present invention has a stable structure and high interface bonding strength. When used as a catalyst, it has good catalytic stability. The specific test results are as follows Figure 6 In addition, the ruthenium-yttrium oxide-based composite material obtained in Example 1 has a high conductivity at 50 mA cm -2 and 100mA cm -2 The overpotential difference under polarization conditions is only 5 mV, which means that when it is used as a catalyst for water electrolysis and hydrogen evolution, the operating condition window is wider and more suitable for commercial applications.
[0120] The above results related to catalytic performance are summarized in Tables 1-2.
[0121] Table 1 Overpotential data of ruthenium-yttrium oxide-based composite materials obtained in Examples and Comparative Examples and commercial platinum-carbon catalysts
[0122] serial number Overpotential mV serial number Overpotential mV Example 1 40 Example 6 47 Example 2 45 Example 7 69 Example 3 53 Comparative Example 1 148 Example 4 67 Pt / C 48 Example 5 69
[0123] Table 2 Related properties of the ruthenium-yttrium oxide-based composite material obtained in Example 1
[0124]
[0125] In summary, the ruthenium-yttrium oxide-based composite material provided by the present invention has high catalytic activity and catalytic stability when used as a hydrogen evolution catalyst, and has a wide operating window. The preparation method used in the present invention is simple in materials, low in price, and easy to operate, and the obtained ruthenium-yttrium oxide-based composite material has excellent catalytic activity and catalytic stability. Therefore, the ruthenium-yttrium oxide-based composite material or the corresponding preparation method provided by the present invention is expected to be widely used in the field of water electrolysis.
[0126] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a ruthenium-yttrium oxide-based composite material, characterized in that: The preparation method comprises the following steps: S1. synthesizing a precursor in an oxide state, wherein the precursor comprises yttrium, ruthenium and iridium; The synthesis method of the precursor comprises the following steps: S1a. The Y salt, Ru salt, Ir salt and complexing agent are mixed in water and dried; The temperature of the mixed reaction is 80-100° C.; the molar ratio of Y, Ru and Ir in the Y salt, Ru salt and Ir salt is 2:2-x:x; and 0<x<2; S1b calcining the solid product obtained in step S1a in an oxygen-containing atmosphere; S2. thermal reduction of the precursor; The thermal reduction is carried out at a temperature of 300-550° C. and for a time of 4-10 hours.
2. The preparation method according to claim 1, characterized in that: The complexing agent includes citric acid; the molar ratio of the molar sum of Y, Ru and Ir in the Y salt, Ru salt and Ir salt to the citric acid is 0.8-1.2:
1.
3. The preparation method according to claim 1, characterized in that: In step S1b, the calcination includes a first stage of constant temperature and a second stage of constant temperature performed in sequence; the temperature of the second stage of constant temperature is 1000-1100°C.
4. The preparation method according to claim 1, characterized in that: In step S2, the thermal reduction atmosphere includes hydrogen.
5. A ruthenium-yttrium oxide-based composite material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The ruthenium-yttrium oxide-based composite material comprises yttrium-ruthenium-iridium oxide and a ruthenium-iridium alloy formed on the surface of yttrium-ruthenium-iridium oxide.
6. The ruthenium-yttrium oxide-based composite material according to claim 5, characterized in that: In the ruthenium-yttrium oxide-based composite material, the molar ratio of yttrium, ruthenium and iridium is 2:2-x:x; and 0<x<2.
7. A hydrogen evolution catalyst, characterized in that The hydrogen evolution catalyst comprises the ruthenium-yttrium oxide-based composite material as claimed in claim 5 or 6.
8. Use of the hydrogen evolution catalyst as claimed in claim 7 in electrolysis of water.
Citation Information
Patent Citations
Preparation method of pure-phase pyrochlore structure Ce2Zr2O7
CN103664192A
Ruthenium-iridium alloy material and preparation method and application thereof
CN115805317A
